Poverty impacts of food price increases in Mali - Minot, Nicholas; Martin, Will (International Food Policy Research Institute, 2023)
Because of low incomes and associated large shares of expenditure on food, Mali is potentially very vulnerable to sharp increases in the prices of key grain staples such as maize and wheat. A first step in understanding the impacts of changes in the prices of these products is to examine developments in their prices on world markets. After a long period of relatively stable prices on world markets, the prices of key food staples began to rise during 2020. This period of price increases, spanning the COVID-19 pandemic and then the price shocks following Russia’s invasion of Ukraine raised serious concerns about the welfare of poor people in countries such as Mali.